Naturally occurring radioactive materials in offshore infrastructure: Understanding formation and characteristics of baryte scale during decommissioning planning - Amy MacIntosh; Daniel T. Oldfield; Dioni I. Cendón; Andrew D. Langendam; Nicholas Howell; Daryl L. Howard; Tom Cresswell (Journal of Hazardous Materials, 2024)

Assessing the ecological impacts of NORM-contaminated scale on marine infauna using sediment microcosms - Amy MacIntosh; Katherine Dafforn; Beth Penrose; Anthony Chariton; Tom Cresswell (Chemosphere, 2023)

Offshore decommissioning horizon scan: Research priorities to support decision-making activities for oil and gas infrastructure - Sarah M. Watson; Dianne L. McLean; Brian J. Balcom; Silvana N.R. Birchenough; Alison M. Brand; Elodie C.M. Camprasse; Jeremy T. Claisse; Joop W.P. Coolen; Tom Cresswell; Bert Fokkema; Susan Gourvenec; Lea-Anne Henry; et al. (Science of The Total Environment, 2023)

Threshold values for the protection of marine ecosystems from NORM in subsea oil and gas infrastructure - Darren J. Koppel; Tom Cresswell; Amy MacIntosh; Rebecca von Hellfeld; Astley Hastings; Stuart Higgins (Journal of Environmental Radioactivity, 2023)

Ecotoxicological effects of decommissioning offshore petroleum infrastructure: A systematic review - Amy MacIntosh; Katherine Dafforn; Beth Penrose; Anthony Chariton; Tom Cresswell (Critical Reviews in Environmental Science and Technology, 2022)

Outcomes from 10 years of biodiversity offsetting - Philip Gibbons; Andrew Macintosh; Amy Louise Constable; Kiichiro Hayashi (Global Change Biology, 2018)
We quantified net changes to the area and quality of native vegetation after the introduction of biodiversity offsetting in New South Wales, Australia—a policy intended to “prevent broad‐scale clearing of native vegetation unless it improves or maintains environmental values.” Over 10 years, a total of 21,928 ha of native vegetation was approved for clearing under this policy and 83,459 ha was established as biodiversity offsets. We estimated that no net loss in the area of native vegetation under this policy will not occur for 146 years. This is because 82% of the total area offset was obtained by averting losses to existing native vegetation and the rate that these averted losses accrue was over‐estimated in the policy. There were predicted net gains in 10 of the 14 attributes used to assess the quality of habitat. An overall net gain in the quality of habitat was assessed under this policy by substituting habitat attributes that are difficult to restore (e.g. mature trees) with habitat attributes for which restoration is relatively easy (e.g. tree seedlings). Long‐term rates of annual deforestation did not significantly change across the study area after biodiversity offsetting was introduced. Overall, the policy examined here provides no net loss of biodiversity: (i) many generations into the future, which is not consistent with intergenerational equity; and (ii) by substituting different habitat attributes, so gains are not equivalent to losses. We recommend a number of changes to biodiversity offsetting policy to overcome these issues.

Cerebral cortical processing of swallowing in older adults - Ruth Martin; Amy Barr; Bradley MacIntosh; Rebecca Smith; Todd Stevens; Donald Taves; Joseph Gati; Ravi Menon; Vladimir Hachinski (Experimental Brain Research, 2006)